INTERNATIONAL NATHIAGALI SUMMER COLLEGE (INSC) ON PHYSICS AND CONTEMPORARY NEEDS - Salahudin, A.; Awais, M. M. (The Nucleus, 2020)
International Nathiagali Summer College (INSC) on Physics and Contemporary Needs has been held every year since 1976, without any break, mostly at the scenic hill resorts near Islamabad, Pakistan. The idea of organizing a College at Nathiagali on regular basis came from the distinguished Nobel Laureate, Late Professor Abdus Salam. These colleges are organized regularly by Pakistan Atomic Energy Commission, and since 2001, in collaboration with National Centre for Physics, Islamabad. The primary purpose of these Colleges is to break the isolation of the scientists in the developing countries by enabling them to interact with an international faculty and their colleagues from the Third World. The scientific activities of INSC aim at the broad coverage of the topics at the frontiers of knowledge in Physics and allied sciences. During the last thirty years more than 520 eminent scientists including six Nobel Laureates shared their knowledge and experience with nearly 5550 scientists from Pakistan and about 880 scientists from as many as 72 developing countries.